Improved energy consumption and smart eco system for mosques in hot arid climates - Amr Sayed Hassan Abdallah (Ain Shams Engineering Journal, 2023)
A smart controls system can control and optimize building services. This article aims to improve mosque energy efficiency. To ensure a comfortable environment, indoor temperatures, lighting performance, and illumination levels were monitored. DIAlux simulation software visualized the lighting for the indoor mosque environment. To assess the impact of smart occupancy sensors on total energy consumption, the DesignBuilder simulation tool was used. Mosque energy consumption can be significantly reduced. By replacing traditional lighting units inside mosques with LEDs, 9 % of the total energy could be saved. Utilizing a smart control plan with the mosque's energy index of 69 kWh/m2/yr could significantly reduce energy consumption. Since there are fewer prayers, except for Friday prayers and Ramadan, energy-regulating smart control systems are applicable during most prayer times. The study focuses on the mosque as a sustainable building and proposes a new concept for mosques to function as energy-efficient buildings in hot arid climate.